2021
DOI: 10.1177/15501477211030122
|View full text |Cite
|
Sign up to set email alerts
|

A mobile sink–integrated framework for the collection of farmland wireless sensor network information based on a virtual potential field

Abstract: To overcome the limitations of traditional data collection methods in large-scale farmland wireless sensor network, in this study, we introduce a mobile sink and propose a virtual potential field-based strategy for mobile sink path planning. Virtual potential field-based strategy constructs a virtual field based on the residual energy, data generation rate, location information and cache urgency of nodes in the monitoring area. The stronger the virtual field, the more attractive it will be to mobile sink, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…An obstacle-aware path for MS is introduced using the cluster-based approach in [36] for WSNs. In [37], Yang et al present a dynamic path for MS using virtual potential fields in WSNs.…”
Section: Path Construction In Obstaclementioning
confidence: 99%
“…An obstacle-aware path for MS is introduced using the cluster-based approach in [36] for WSNs. In [37], Yang et al present a dynamic path for MS using virtual potential fields in WSNs.…”
Section: Path Construction In Obstaclementioning
confidence: 99%
“…The results showed that AI-based approaches could improve WSN performance with regard to obstacle avoidance and coverage. A sink-hole problem for WSNs is addressed using an information-based clustering approach in [28]. The [29] paper uses clustering for an obstacle-aware approach to WSN data acquisition using MS, whereas the [30] paper uses trajectory optimization for WSN data collection.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, a path-based equalization algorithm (PEABR) is proposed to adjust the path of the mobile Sink, and the result shows the feasibility and effectiveness of the algorithm. In order to overcome the limitations of traditional data collection methods in large-scale farmland wireless sensor networks, Yang et al [ 27 ] introduced mobile Sink and proposed a path planning strategy for mobile Sink based on virtual potential field. The results show that the method has good transmission efficiency and prolongs the lifetime of the network.…”
Section: Related Workmentioning
confidence: 99%